Alleged case of blasphemy on podcast: Forensic linguistic analysis - Novi Eka Susilowati; Sailal Arimi; Surahmat Surahmat; Fardan Mahmudatul Imamah (Fakultas Sastra Universitas Negeri Malang, 2023)
This study aimed to analyze the linguistic features that allegedly contained elements of blasphemy in Jenderal Dudung Abdurrachman's (JDA) speech. The analysis was carried out using a forensic linguistic perspective. This research data is in the form of JDA utterances delivered in a broadcast conducted with Deddy Corbuzier (DC). Based on a forensic linguistic analysis of the text of JDA's conversation with DC on Deddy Corbuzier's podcast, it can be concluded that JDA's linguistic evidence does not support blasphemy but a lack of knowledge in religion, especially in matters of faith. Due to the lack of knowledge of religion, JDA interprets religion and personifies God according to his understanding. In JDA's speech, there is also no intention to tarnish religion because the controversial JDA's speech cannot be interpreted partially but can be interpreted with other speeches. If it is related to other utterances, it can be concluded that there is no intention of JDA to tarnish religion. However, there are efforts by JDA to invite audiences to follow JDA's understanding and interpretation of religion.Dugaan kasus penodaan agama di podcast: Analisis linguistik forensikTujuan penelitian ini adalah menganalisis fitur kebahasaan yang diduga memuat unsur penodaan agama dalam tuturan Jenderal Dudung Abdurrachman (JDA). Analisis dilakukan dengan menggunakan perspektif linguistik forensik. Data penelitian ini berupa tuturan JDA yang disampaikan dalam siniar yang dilakukan bersama Deddy Corbuzier. Berdasarkan analisis linguistik forensik atas teks perbincangan JDA dengan DC di siniar DC, dapat disimpulkan bahwa tuturan JDA bukti-bukti kebahasaan tidak mendukung adanya penodaan agama, melainkan kurangnya pengetahuan dalam beragama, terutama dalam hal akidah. Akibat kurangnya pengetahuan dalam beragama tersebut, JDA menafsirkan agama dan mempersonifikasi Tuhan sesuai dengan pemahamannya. Dalam tuturan JDA juga tidak terdapat niat untuk menodai agama karena tuturan JDA yang kontroversial tersebut tidak dapat dimaknai secara parsial, melainkan dimaknai secara menyeluruh dengan tuturan-tuturan lain. Jika dikaitkan dengan tuturan yang lain, dapat disimpulkan bahwa tidak ada niat JDA untuk menodai agama. Meski demikian, terdapat upaya JDA untuk mengajak audiens agar mengikuti pemahaman dan penafsiran JDA tentang agama.